2023
DOI: 10.3389/fimmu.2023.1114663
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analyses reveal the dynamic functions of Itgb2+ microglia subclusters at different stages of cerebral ischemia-reperfusion injury in transient middle cerebral occlusion mice model

Abstract: IntroductionThe underlying pathophysiological mechanisms of cerebral ischemia reperfusion injury (CIRI) is intricate, and current studies suggest that neuron, astrocyte, microglia, endothelial cell, and pericyte all have different phenotypic changes of specific cell types after ischemic stroke. And microglia account for the largest proportion after CIRI. Previous transcriptomic studies of ischemic stroke have typically focused on the 24 hours after CIRI, obscuring the dynamics of cellular subclusters throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Consistently, ITGB2 has been shown as a target of KLF5 in breast cancer cells 10 . ITGB2‐positive microglia subcluster has been recently related to energy metabolism, cell cycle, angiogenesis, neuronal myelin formation, and repair in response to cerebral I/R injury 11 . Because myocardin‐related transcription factor A has been identified to regulate the transcriptional level of ITGB2 to expedite macrophage infiltration and cardiac hypertrophy in mice 12 and macrophage‐mediated excessive inflammatory response is of great importance to hepatic I/R injury, 13 we hypothesized that Sevo elicited protection to the livers with I/R injury by controlling macrophage infiltration via the KLF5/ITGB2 axis.…”
Section: Introductionmentioning
confidence: 76%
“…Consistently, ITGB2 has been shown as a target of KLF5 in breast cancer cells 10 . ITGB2‐positive microglia subcluster has been recently related to energy metabolism, cell cycle, angiogenesis, neuronal myelin formation, and repair in response to cerebral I/R injury 11 . Because myocardin‐related transcription factor A has been identified to regulate the transcriptional level of ITGB2 to expedite macrophage infiltration and cardiac hypertrophy in mice 12 and macrophage‐mediated excessive inflammatory response is of great importance to hepatic I/R injury, 13 we hypothesized that Sevo elicited protection to the livers with I/R injury by controlling macrophage infiltration via the KLF5/ITGB2 axis.…”
Section: Introductionmentioning
confidence: 76%
“…Cluster 1 is involved in inflammation, cluster 3 is associated with metabolic processes, and clusters 6 and 7 are involved in glial cell differentiation, gliogenesis, neurogenesis, and synapses. 21 Zheng et al also found that microglial cells exhibit cellular diversity in five different subtypes after stroke and divided these into five clusters. Cluster MG 0 primarily originates from the sham-operated group and is characterized by high expression of genes such as P2ry12, Selplg, Tmem119, Gpr34, Siglech, Olfm13, P2ry13, Csf1r, and Hexb.…”
Section: Zheng Et Al Utilized Scrna-seq To Analyze Cell Populations I...mentioning
confidence: 99%
“…The activation of microglial cells is the initial step in the central nervous system inflammatory response, followed by the infiltration of immune cells, such as neutrophils, macrophages/monocytes, natural killer cells, and T cells, and the activation of neurons 26 . In a study by Zeng et al., the percentage of activated microglial cells was significantly higher than that in the sham‐operated group on the first, third, and seventh day after AIS 21 . Moreover, activated microglial cells produce various mediators, including inducible nitric oxide synthase (iNOS), nitric oxide (NO), 27,28 pro‐inflammatory cytokines (such as TNF‐a), and anti‐inflammatory cytokines (such as TGF‐a), 29 collectively leading to complex immune reactions in the brains of patients with stroke, 16,30–32 including reactions with contradictory effects 33–35 .…”
Section: Microgliamentioning
confidence: 99%
See 2 more Smart Citations